An improved explants culture method: Sustainable isolation of keloid fibroblasts with primary characteristics. (14th October 2022) - He, Yan; Zhang, Shengpeng; Bao, Wu; Xue, Yi; Yin, Bin; Cheng, Xialin; Zhang, Zexin; Jia, Chiyu
Abstract: Background: Keloid (KD) is a complex fibroproliferative disease, but the exact mechanisms underlying keloid pathogenesis remain to be elucidated. The primary keloid fibroblasts (KFs) culture in vitro has always been a fundamental measure to study the pathogenesis of keloid. However, the traditional primary culture methods have some limitations, such as a long culture cycle, low specimen utilization rate and so on. Aims: Improve the keloid explants culture method sts. Materials & Methods: We proposed an improved new "explants multiple culture method"—reusing keloid explants for primary culture and harvesting the primary KFs in specific culture times. Meanwhile, the purity, proliferation, apoptosis, migration, invasion, extracellular matrix synthesis, and some fibrosis and inflammation‐related proteins of KFs obtained from the first, fifth, and tenth explants cultures were detected. Results: The results showed that the culture cycle of this new method (Cell Isolation: 2.67 ± 0.86 days, Explants removal: 8.83 ± 0.79 days, Cell Passage: 15.17 ± 1.39 days) was significantly shorter than that of the traditional method (Cell Isolation: 8.67 ± 1.84 days, Explants removal: 17.67 ± 2.17 days, Cell Passage: 22.67 ± 1.84 days). No significant difference was observed between the phenotypes of the fibroblasts obtained from the first explants culture and cultures less than 10 times ( p  > 0.05). Disscussion: Taken together, this study provides an effective method for the primary culture of KFs with a higher specimen utilization rate and shorter culture cycle. Conclusion: This method breaks through the limitation of traditional explants culture requiring a large number of keloid specimens and provides a rich source of KFs for the study of keloid.